Computer System Usability Questionnaire (CSUQ) dalam Usability Testing Aplikasi Perkumpulan Penggiat Programmer Indonesia (P3I) - M. Yusuf Febrianto; Fenilinas Adi Artanto; Dani Mutaqo; Aqika Ari Yogiana (Yayasan Pendidikan Penelitian Pengabdian ALGERO, 2025)
The development of Information and Communication Technology has driven innovation in learning media, including the Indonesian Programmer Activists Association (P3I) which provides online training services through the Online Learning Information System Application (SIPO). To provide quality learning services, a usability evaluation of the P3I application was conducted using the Computer System Usability Questionnaire (CSUQ) method. The CSUQ method focuses on evaluating three aspects, namely System Usefulness, Information Quality, and Interface Quality. This study uses a quantitative approach with the Snowball sampling technique on 50 respondents from a total population of 70 active P3I members. Data analysis was carried out using the Partial Least Square - Structural Equation Modeling (PLS-SEM) method through smartPLS software. The test results show that the indicators in the CSUQ model have good validity and reliability, with most loading factor values ​​≥ 0.7 and Average Variance Extracted (AVE) and Composite Reliability values ​​that have met the standards. The analysis results also show that System Usefulness, Information Quality, and Interface Quality together have given an influence of 80.5% on the Usability of the P31 Application. These results indicate that the P3I application has been able to provide benefits to its users and these findings can be used as input in further system development to improve the user experience in online learning.